If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1y + 3y + -5x = 0 Reorder the terms: 2x + -5x + -1y + 3y = 0 Combine like terms: 2x + -5x = -3x -3x + -1y + 3y = 0 Combine like terms: -1y + 3y = 2y -3x + 2y = 0 Solving -3x + 2y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. -3x + 2y + -2y = 0 + -2y Combine like terms: 2y + -2y = 0 -3x + 0 = 0 + -2y -3x = 0 + -2y Remove the zero: -3x = -2y Divide each side by '-3'. x = 0.6666666667y Simplifying x = 0.6666666667y
| (2cosx)(3sinx)-3=0 | | (3x-2)(3x-8)= | | 53.50/30 | | 36n=35n | | 3/2x-4/5x/1/3-2/x | | 5-2(T+4)=(3T+12) | | X+6=-40 | | Ln(x+12)=8 | | 972=x(3x) | | 7x+8y+(-8y)+(-9x)= | | 1/4=y=12 | | 40x^2+116x+84= | | -8n^2-12n+14=8 | | -x-178=5x+176 | | 700=29*24 | | -27.6=18.1+m | | X^2-17=17 | | 2k^2=49+7k | | -9=-m | | -27.6=18.1m | | -n^2-15n+72=-9n | | 130+2x=9x-129 | | 5x+20forx=1.5 | | X^2-20=-3 | | -6+3k-4K+7= | | 4(2x-3)(3x-4)= | | (Y-5)3=20 | | 16x-8-8x=24 | | 30x^2-40x-40= | | 5(x+2)=-2(1-4x)-6x | | X^2-7=103 | | (7-8i)+(-12-4i)=0 |